DISCOURSE, KNOWLEDGE, AND POWER ON THE SOCIAL NETWORK TWITTER: A SURVEY OF HIGH SCHOOL STUDENTS POSTINGS ABOUT THE COVID-19 PANDEMIC - Adams, Adair; Trintin, Morgana de Almeida (Revista Missioneira, 2022)
The text objectifies to present an analysis about the confronts of the Covid-19 pandemic expressed by High School students on the social network Twitter. Whit qualitative and bibliographic bias, the postings interpretation will have as basis and horizon the relations between discourse, knowledge, and power in “The order of Discourse”, from Michel Foucault. The expressions and comprehensions diversity publicized on social media disclose the ways of confronting the pandemic and the social and cultural issues of society in the 21st century. Our bet is to collaborate in the understanding of students’ discourses that are one step away from the entrance of the adult world, to which they will be soon responsible.